Pemberdayaan Masyarakat Desa Batuphat Timur Melalui Keterampilan Pengolahan Dendeng Ikan Bandeng - Rachmawati Rusydi; Salamah Salamah; Munawwar Khalil; Mainisa Mainisa (JPM: Jurnal Pengabdian Masyarakat, 2020)
Empowerment of women at East Batuphat District is still less efforts in increasing their family income. This training aims to empower the women at East Batuphat District in processing the yield of estuary ponds which are at that district. There were several steps of this training, such as preparing materials and equipments, surveying knowledge and understanding of participants, demonstrating the processing of milkfish dendeng, Training the processing of milkfish dendeng by participants, and surveying the quality of milkfish dendeng product. The results of the training were the percentage of those women which understood about fishery processed products and milkfish dendeng was increased after training. This training gave some skills to those women in processing milkfish dendeng and it became to new source of their income. Generally, organoleptical assessment of milkfish dendeng was in accordance with the characteristics of dendeng.